Recurrent spontaneous subserosal hematoma of ileum causing intestinal obstruction in a patient with menkes disease: A case report. Issue 37 (September 2016) - Weng, Shu-Chao; Hsu, Chyong-Hsin; Wang, Nien-Lu; Lin, Shuan-Pei; Jiang, Chuen-Bin
Abstract: Background: Menkes disease (MD) is a disorder of copper metabolism due to ATP7A gene mutation that leads to severe copper deficiency. Deformed blood vessels can be found in many parts of the body, and intracranial hematoma is generally reported. Methods: We report a Taiwanese boy with MD who had recurrent spontaneous subserosal hematoma of ileum presenting as intestinal obstruction, with the 2 episodes 23 months apart. The patient returned to the usual physical status after surgical removal of the hematoma. Results: The defective copper metabolism causes dysfunction of a plenty of copper-dependent enzymes, giving rise to unique kinky hair appearance, progressive neurodegeneration, and connective tissue abnormalities. To our knowledge, this is the first report on recurrent subserosal hemorrhage of intestine in MD. Conclusion: Owing to the fragile structure of blood vessels, subserosal hematoma should be considered when patients with MD having intestinal obstruction.